Dr. Pouyan Darbani — Deep Plane Facelift — Tehran - Darbani, Pouyan (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Pouyan Darbani, practicing in Tehran, Iran. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003074; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; iran; tehran